2015
DOI: 10.1175/jas-d-14-0358.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Response to the QBO in the Northern Winter Stratosphere: Signatures in Wave Forcing and Eddy Fluxes of Potential Vorticity

Abstract: Wave-mean flow interactions associated with the Holton-Tan effect (HTE), whereby the tropical quasibiennial oscillation (QBO) modulates the Northern Hemisphere wintertime stratospheric polar vortex, are studied using the ERA-Interim dataset. Significant evidence of the HTE in isentropic coordinates is found, with a weaker and warmer polar vortex present when the lower-stratospheric QBO is in its easterly phase (QBOe). For the first time, the authors quantify the QBO modulation of wave propagation, wave-mean fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 74 publications
(97 reference statements)
5
68
0
1
Order By: Relevance
“…13 could be interrupted by other processes. For instance, in the event when the lower-stratospheric QBO is in its easterly phase, the enhanced BPWs in the lower and middle stratosphere would lead to a reduction of the PV gradient along the polar vortex edge (White et al 2015(White et al , 2016. These lower-level QBOinduced BPWs would then inhibit upward wave propagation, shielding the upper stratosphere from BPWs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 could be interrupted by other processes. For instance, in the event when the lower-stratospheric QBO is in its easterly phase, the enhanced BPWs in the lower and middle stratosphere would lead to a reduction of the PV gradient along the polar vortex edge (White et al 2015(White et al , 2016. These lower-level QBOinduced BPWs would then inhibit upward wave propagation, shielding the upper stratosphere from BPWs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, when the waves are resonantly excited, we would also expect the seasonal averages of negative daily u 0 y 0 and/ or y 0 T 0 to be sufficiently larger than their climatology. The momentum and heat fluxes are used instead of the E-P fluxes F (f) and F (z) because they do not involve static stability u z , which was found to introduce relatively large biases in the upper stratosphere during data assimilation (Lu et al 2015).…”
Section: E Diagnostics For Wave Reflection and Resonancementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the direct impact of the QBO on the underlying tropospheric circulation in the tropics and sub-tropics is of interest (Giorgetta et al 1999;Collimore et al 2003;Ho et al 2009;Liess and Geller 2012;Nie and Sobel 2015) and recent studies have shown that the QBO modulates the amplitude of the Madden Julian Oscillation, which may lead to improved predictability of MJO under QBO-E conditions Marshall et al 2016;Son et al 2017;Nishimoto and Yoden 2017). 25 One mechanism for QBO influence at the surface is through the modulation of planetary wave propagation in winter by refraction or horizontal reflection of the waves towards (away from) high latitudes under QBO-E (QBO-W) conditions (Holton and Tan 1980;Garfinkel et al 2012;Watson and Gray 2014;White et al 2015). This influence route (the 'polar route') modulates the strength of the polar vortex, and there have been many studies demonstrating that the polar 30 vortex can subsequently influence the underlying tropospheric circulation and surface temperature / pressure distributions Thompson et al 2002, Mitchell et al 2013.…”
mentioning
confidence: 99%